Complementation of ROS scavenging secondary metabolites with enzymatic antioxidant defense system augments redox-regulation property under salinity stress in rice - Banik, Nabanita (Physiol Mol Biol Plants, 2020)
The RP-HPLC based comparative quantification of some important redox sensitive phenolic acids and flavonoids revealed overall greater elicitation of chalcone synthase related flavonoid biosynthetic pathway, concomitant with the greater utilization of cinnamic acid for the seedlings of the salinity resistant rice cultivar Patnai as compared to susceptible cultivar IR29 grown under post imbibitional salinity stress (PISS). When compared, the cultivar Patnai further exhibited significantly better antioxidant-coupled redox-regulation by up regulating ascorbate–glutathione pathway and reducing the expression of oxidative deterioration under PISS as compared to its counterpart, the cultivar IR29. A model for redox homeostasis in which complementation of action of ROS scavenging secondary metabolites with enzymatic antioxidant defense at metabolic interface necessary for maintenance of the redox homeostasis to combat salinity stress has been proposed.